Fiscal Incidence on the Island: Grenada's Fiscal System and Its Incidence - Gustavo J. Canavire Bacarreza; Guillermo Gómez Aliaga; Chevanne Britton; Fernando Rios-Avila; Wilson Jiménez Pozo; Silvia Granados Ibarra; Ran Li (Institute of Labor Economics (IZA), 2024)
This paper examines the distributional effects of fiscal policy in Grenada. Using data from the 2017–2018 Living Conditions and Household Budgets Survey and following the Commitment to Equity (CEQ) analysis framework, we estimate the effects of fiscal policy interventions on inequality and poverty. Specifically, we analyze the distributional incidence of direct and indirect taxes, direct transfers provided by the social transfers and the school feeding programs, and in-kind transfers generated by public services in health and education. The results show that Grenada has a tax system that is neutral on the VAT side and progressive on the personal income tax side. Furthermore, direct transfers make a modest contribution to poverty reduction and are almost neutral in their distributive impact. The results contribute to the understanding of who bears the burden of taxation and benefits from transfers and of how Grenada's fiscal system can improve its redistributive effect.
Keywords: D31; H11; H22; H5; I14; I24; I3; O54; 330; fiscal incidence; poverty; inequality; taxes; social transfers; public expenditure; public revenue